Report on SCOR Working Group 38 (with SCAR): special studies in circumpolar waters south of 40°S - IOC. Assembly, 8th session, Paris, 1973; Deacon, Sir George Edward Raven (10 Sept. 1973, 1973)
Meeting paper submitting a report on the activities of SCOR Working Group No. 38 (with SCAR) - Refers mainly to studies of the Antarctic Ocean and to the role of oceanographic buoys and research ships